The influence of heat treatment on the quality of screen printed textile substrates - Kašiković,Nemanja (2017)
ABSTRACT During exploitation, textile products printed with screen printing technique are quite often exposed to various influences, one of which is a heat treatment- firstly during the production process and later on when ironing. Heat is simultaneously affecting deposited colorants (ink) on the surface of the substrate material, as well as textile fibers in the material structure. As a result, colorimetric characteristics of printed colorants are changed. The research presented in this paper aims to determine the influence of heat treatment on color changes of screen printed textile substrates, observed in CIE L*, a*, b* color space. Macro non-uniformity of the printed cotton textile materials was analyzed as a function of temperature levels applied during thermal treatments and textile material characteristics, as well as mesh counts of screens used in the printing process. The results show that thermal treatment affects the color change of printed samples.